Procedural discourse performance in adults with severe traumatic brain injury at 3 and 6 months post injury. (28th January 2018) - Stubbs, Elin; Togher, Leanne; Kenny, Belinda; Fromm, Davida; Forbes, Margaret; MacWhinney, Brian; McDonald, Skye; Tate, Robyn; Turkstra, Lyn; Power, Emma
ABSTRACT: Background : There is limited research on communicative recovery during the early stages after a severe traumatic brain injury (TBI) in adults. Methods and procedures : In the current study 43 people with severe TBI described a simple procedure at 3 and 6 months post injury and this was compared to the description provided by 37 healthy speakers. Linguistic productivity and the presence of macrostructural discourse elements were analysed. Main outcomes and results : No change occurred in productivity in the TBI group between the two time points. There was increased use of relevant information (macrostructure) over time for the TBI group, reflecting improvement. People with TBI differed from controls in speech rate and in two out of three macrostructural categories at both time points, indicating difficulties even after 12 weeks of recovery. Conclusions : Overall, the quality, rather than the quantity of discourse was disordered for participants with TBI. Findings indicate that procedural discourse is sensitive to discourse deficits of people with TBI and can be used to map recovery during the sub-acute phase.